Marketization, Social Protection, Emancipation: Toward a Neo-Polanyian Conception of Capitalist Crisis - Fraser, Nancy (Business as Usual: The Roots of the Global Financial Meltdown, 2011)
BOOK ABSTRACT: Situates the current crisis in the historical trajectory of the capitalist world-system, showing how the crisis was made possible not only by neoliberal financial reforms but by a massive turn away from manufacturing things of value towards seeking profit from financial exchange and credit. Much more basic than the result of a few financial traders cheating the system, this is a potential historical turning point. In original essays, the contributors establish why the system was ripe for crisis of the past, and yet why this meltdown was different. The volume concludes by asking whether as deep as the crisis is, it may contain seeds of a new global economy, what role the US will play, and whether China or other countries will rise to global leadership. Contributors include: Giovanni Arrighi, Gopal Balakrishnan, Manuel Castells, Daniel Chirot, Fernando Coronil, Nancy Fraser, James K. Galbraith, David Harvey, Caglar Keyder, Beverly J. Silver, and Immanuel Wallerstein. The three volumes can purchased individually or as a set. Business as Usual is the first part of a trilogy comprised of the first three books in the Possible Future series. Volume 1: Business as UsualVolume 2: The Deepening CrisisVolume 3: Aftermath The three volumes are linked by a common introduction and can be purchased individually or as a set.
Philosophy; Political Science
Keywords: capitalism; emancipation; feminism; gender; welfare state

A Triple Movement? - Fraser, Nancy (New Left Review, 2013)
Philosophy; Political Science
Keywords: double movement; social protection; triple movement

Fortunes of Feminism: From State-Managed Capitalism to Neoliberal Crisis - Fraser, Nancy (Verso Books, 2013)
Charts the history of women’s liberation and calls for a revitalized feminism.Nancy Fraser’s major new book traces the feminist movement’s evolution since the 1970s and anticipates a new—radical and egalitarian—phase of feminist thought and action.During the ferment of the New Left, “Second Wave” feminism emerged as a struggle for women’s liberation and took its place alongside other radical movements that were questioning core features of capitalist society. But feminism’s subsequent immersion in identity politics coincided with a decline in its utopian energies and the rise of neoliberalism. Now, foreseeing a revival in the movement, Fraser argues for a reinvigorated feminist radicalism able to address the global economic crisis. Feminism can be a force working in concert with other egalitarian movements in the struggle to bring the economy under democratic control, while building on the visionary potential of the earlier waves of women’s liberation. This powerful new account is set to become a landmark of feminist thought.
Philosophy; Political Science
Keywords: critical theory; feminism; feminist theory; triple movement

Capitalism: A Conversation in Critical Theory - Fraser, Nancy; Jaeggi, Rahel (John Wiley & Sons, 2018)
In this important new book, Nancy Fraser and Rahel Jaeggi take a fresh look at the big questions surrounding the peculiar social form known as “capitalism,” upending many of our commonly held assumptions about what capitalism is and how to subject it to critique. They show how, throughout its history, various regimes of capitalism have relied on a series of institutional separations between economy and polity, production and social reproduction, and human and non-human nature, periodically readjusting the boundaries between these domains in response to crises and upheavals. They consider how these “boundary struggles” offer a key to understanding capitalism’s contradictions and the multiple forms of conflict to which it gives rise. What emerges is a renewed crisis critique of capitalism which puts our present conjuncture into broader perspective, along with sharp diagnoses of the recent resurgence of right-wing populism and what would be required of a viable Left alternative. This major new book by two leading critical theorists will be of great interest to anyone concerned with the nature and future of capitalism and with the key questions of progressive politics today.
Philosophy; Political Science
Keywords: boundary struggle; capitalism; political philosophy; triple movement